STRATEGI PENCEGAHAN KEJAHATAN TERORISME DI INDONESIA MELALUI PEMBANGUNAN SOSIAL (CRIME PREVENTION SOCIAL DEVELOPMENT) - eko borneo yulanderi (Jurnal Pro Justitia (JPJ), 2020)
ABSTRACT Crime Prevention Social Development (CPSD) is a method that recognizes that social, economic, and cultural processes have a strong contribution to the incidence of crime and victims. The CPSD seeks to bridge the gap between criminal policies and programs that support social progress for individuals, families and the wider community. This study uses a juridical normative and juridical empirical approach. The type of data used is primary data and secondary data. Primary data obtained from interview and secondary data sourced from literature study. Studies show that the implementation of the Crime Prevention Social Development (CPSD) strategy includes Individual level strategies (focusing on individual issues that can put them in situations that put them at risk of being involved in crime), Family Oriented Strategies oriented families that provide parenting support and training to young parents, children strengthen family capacities, and create healthy family environments where children can be well cared for), Community Level Strategies (seeks to strengthen local communities capacity to prevent the occurrence crimes in the region including programs that provide social and cultural opportunities). The suggestion in this research is the Crime Prevention Social Development (CPSD) strategy in its system not only for local people but also to pay attention to foreign aspect because of the nature of the trans-national terrorism that becomes the point the start of the development of networks of other terrorist groups. Keywords: Crime Prevention, Social, Development, Terrorism.